2006
DOI: 10.1159/000094421
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and Substance Use Disorders in a Community Sample of Adolescents and Young Adults: Incidence, Age Effects and Patterns of Use

Abstract: Objective: We present the prevalence and incidence rates of alcohol, nicotine, and illicit substance use, abuse, and dependence in a sample of German adolescents and young adults. Patterns of onset, cohort trends, and use of various substance classes are also analyzed. Method: A prospective longitudinal epidemiological study with a representative sample of adolescents and young adults (n = 3,021; baseline age range = 14–24 years) was conducted in Munich, Germany. Participants were assessed between 1995 and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 52 publications
(28 reference statements)
6
30
0
1
Order By: Relevance
“…We found that younger youths started using tobacco, cannabis and other illicit drugs at an earlier age than older youths, which is consistent with studies conducted in the Netherlands, Germany and the United States (Johnson et al, 2006;Monshouwer et al, 2005;Perkonigg et al, 2006). As other researchers,…”
Section: Age Of Onsetsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that younger youths started using tobacco, cannabis and other illicit drugs at an earlier age than older youths, which is consistent with studies conducted in the Netherlands, Germany and the United States (Johnson et al, 2006;Monshouwer et al, 2005;Perkonigg et al, 2006). As other researchers,…”
Section: Age Of Onsetsupporting
confidence: 91%
“…In recent years, rates of adolescent substance use appear to have increased across industrialized countries (Bachman et al, 1998;. Moreover, there is evidence that youths start using psychoactive substances at earlier ages than in the past (Monshouwer et al, 2005;Perkonigg et al, 2006). This is of concern because adolescents who regularly use psychoactive substances are at high risk of substance-related abuse or dependence, as well as employment problems and delinquency later in life (Ellickson et al, 2003;Perkonigg et al, 1999;Riala et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although findings were similar to prevalences reported among young adults in Canada, 33 Europe, 30 Australia, 34 and the United States, [35][36][37][38] there was a high level of psychoactive substance use among NDIT Study participants irrespective of water-pipe use.…”
Section: Discussionsupporting
confidence: 76%
“…Across industrialized countries, tobacco, alcohol and cannabis use levels in young adults are high [1,2,3]. This may in part be because the period between 18 and 30 years of age is characterized by role exploration, high accessibility of psychoactive substances and high tolerance of addictive behaviors [4,5].…”
Section: Introductionmentioning
confidence: 99%